Epidemiology and Incidence of Orthopedic Fractures in the Military of the Republic of Korea - Sung Jin An; Sang Hyun Lee; Gi-Ho Moon (Journal of Trauma and Injury)
Purpose Fractures are common in the military population, but limited studies have investigated the incidence of fractures among Korean military personnel. Hence, this study aimed to clarify this issue. Methods Eligible subjects were patients who had sustained a fracture and were registered in the N-DEMIS (the medical records system of participating hospitals) from June 2017 to May 2019. Fractures were categorized according to the fracture site, patients’ age, sex, and type of duty. Results In total, 23,687 patients with 23,981 fractures were included. There were 216 patients with multiple fractures, of whom 156 had fractures at two sites, 42 had fractures at three sites, and 18 had fractures at four sites. Of the 23,687 patients, 23,340 were men and 347 were women. The incidence of fractures in men and women was 12.96 per 1,000 person-years and 0.19 per 1,000 person-years, respectively. In terms of the broad location of fractures, the percentage of fractures was the highest in the hand, followed by the foot and lower leg. When the location of fractures was analyzed more specifically, the percentage of fractures was the highest in the phalanx (thumb and fingers), followed by the ankle and metacarpal bones. Conclusions Hand, foot, ankle, and wrist fractures were the most commonly encountered fractures in the Korean military population. To prevent the loss of combat power due to non-battle-related injuries, thorough preparation is necessary, including protective equipment and preliminary training for areas with a high frequency of fracture occurrence.